A Review on Bone Tumor Management: Cutting-Edge Strategies in Bone Grafting, Bone Graft Substitute, and Growth Factors for Defect Reconstruction - Sakdejayont S; Chobpenthai T; Suksirivecharuk P; Ninatkiattikul IF; Poosiripinyo T (Orthopedic Research and Reviews)
Siwat Sakdejayont,1 Thanapon Chobpenthai,1 Ploy Suksirivecharuk,1 I-Fan Ninatkiattikul,1 Thanate Poosiripinyo2 1Princess Srisavangavadhana Faculty of Medicine, Chulabhorn Royal Academy, Bangkok, Thailand; 2Department of Orthopaedics, Khon Kaen Hospital, Khon Kaen, ThailandCorrespondence: Thanapon Chobpenthai, Princess Srisavangavadhana Faculty of Medicine, Chulabhorn Royal Academy, 906 Kamphaengphet 6 Road, Talat Bang Khen Lak Si, Bangkok, 10210, Thailand, Tel +662-576-6000, Fax +662-576-6904, Email thanapon.cho@cra.ac.thAbstract: Bone tumors present complex challenges in orthopaedic oncology, requiring precise management strategies to restore skeletal integrity and function with minimal morbidity. Traditional autologous bone grafting has been the gold standard due to its osteogenic, osteoconductive, and osteoinductive properties. However, limitations such as donor site morbidity and graft availability have prompted the development of alternative approaches.This review evaluates contemporary approaches in bone tumor management, focusing on advancements in bone grafting techniques, bone graft substitutes (eg, ceramics, polymers, bioactive materials), and growth factor-based therapies. The efficacy and safety of these substitutes are compared with autografts, examining their potential benefits and drawbacks.Recent innovations in bone graft substitutes show promise in overcoming autograft limitations. Ceramic, polymer, and bioactive materials offer diverse properties that may enhance bone regeneration. Growth factor-based therapies, including bone morphogenetic proteins (BMPs) and vascular endothelial growth factor (VEGF), have revolutionized bone healing by stimulating osteogenesis and angiogenesis.Plain Language Summary: The review compares efficacy and safety of bone graft substitutes with traditional autografts, highlighting their potential benefits and challenges, thus helping clinicians choose the most suitable option for bone tumor management.Autologous bone grafting remains the gold standard; its limitations—such as donor site morbidity and limited graft availability—have driven the development of alternative approaches like bone graft substitutes and growth factor-based therapies.Advances in materials such as ceramics, polymers, and bioactive substances offer promising solutions for bone defect reconstruction, providing enhanced properties for bone regeneration and overcoming the shortcomings of autografts.Growth factor therapies, including Bone Morphogenetic Proteins (BMPs) and Vascular Endothelial Growth Factor (VEGF), transform bone healing by stimulating osteogenesis and angiogenesis, improving the recovery and function of the affected bone.Integrating bone graft substitutes and growth factor therapies, there is significant potential to improve clinical outcomes in orthopaedic oncology, offering more effective bone defect reconstruction and enhanced quality of life for patients.Keywords: Bone tumors, bone graft, tumor management, defect reconstruction, growth factor